PERSEPSI TENTANG RELAKTASI DARI IBU YANG TELAH MELAKUKAN RELAKTASI di SAMPANG – INDONESIA: Studi Fenomenologi Deskriptif - Imroatus Sholihah; Zainun Wahida Fithriani (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2023)
Background: Most of the breastfeeding problems such as relactation experience stem from the psychological condition of the women who experience it. Those stress conditions affect the brain loci that control the perception of health. Perception’s problem is a very broad and complex. Therefore, interesting to understanding about perceptions of relactation experiences in women who failed to provide exclusive breastfeeding through qualitative methods. Method: The research was conducted using descriptive phenomenology on 10 informants through semi-structural interviews. Result: Seven themes obtained namely (a) Knowledge about Breastfeeding (b) Support obtained during breastfeeding (c) Role of health workers in the breastfeeding process (d) Postnatal psychological condition (e) Mother's Breastfeeding History (g) The role of social media and relations in the breastfeeding process (h) Implementation of Early Initiation of Breastfeeding (IMD) in the delivery place. Discussion: Various components have mutual implications for the relactation have done such as due to a lack of knowledge about breastfeeding and the existence of self-perceptions about postpartum psychological conditions which tend to be moody. The view that the mother had previously breastfed and was considered to have more knowledge was a trigger for women to feel safer when following their mother. In addition, self-perception also has implications for self-confidence to breastfeed. The closest environment and the most frequent contact, namely health workers, how the nuclear family supports women physically and mentally after childbirth, the implementation of IMD in the delivery center, and access to breastfeeding information through social media have implications for the success of relactation.